MODEL SISTEM PENDIDIKAN PONDOK PESANTREN MODERNALUMANAATERINTEGRITAS PADA PEMBERDAYAAN SUMBER DAYAALAM DALAM MENCAPAI PRESTASI AKADEMIS DAN NON AKADEMIS - Nurwulan Kusuma Devi; Putri Sarirati (Sekolah Tinggi Manajemen IMMI, 2020)
Empowerment of Natural Resources in the education environment provides positive values for the environment and provides its own economic contribution for institution. Environmental factors also have added value for students in carrying out the teaching and learning process so that researchers will find out whether the education model by integrating on empowering aspects of natural resources will provide creativity to students and also how integrated education patterns in natural resource empowerment aspects will produce results of academic and non-academic achievements. In addition, the results of this study can provide inspiration for prospective educators to find out about education models that integrate into Natural Resources at school locations and for education can be used as role models of education in the future. Therefore researchers will conduct research with a qualitative research method approach. The use of data collection tools in the form of interview guide sheets, observation sheets, documentation, and questionnaires. The interview model is carried out with open and structured interview techniques. Interview guides that have been arranged, but if there are questions that are developing but are still relevant to aspects of the research will be adjusted to the answers of the subjects or respondents. The distribution of questiionnairs about students’s satisfaction with the results of the antpes education that show more than 70% of them are happy and motivated to learn many things and obey the rules tht have been announced . This natural resource which is one of the sources of income in Modern Islamic Boarding School teaches the students the balance of life and is implemented with daily activities that are always guided by making very significant result in the academic achievement and the non academic achievement .